Influence of conduit and topography complexity on spine extrusion at Shiveluch volcano, Kamchatka - Walter Thomas R.; Zorn Edgar U.; Harnett Claire E.; Shevchenko Alina V.; Belousov Alexander; Belousova Marina; Vassileva Magdalena S. (My University, 2022)
Most volcanic eruptions occur through magma pathways that resemble tube-like conduits fed from magma sources at depth. Here we combine remote sensing observations with both analog and numerical experiments to describe the extrusion of a spine at the Shiveluch lava dome, Kamchatka (Russian Far East) in April-October 2020. We show that spine growth is preceded by bulging of the dome surface, followed by extrusion in an asymmetric manner. The spine then elongates along a previously identified fracture line and bends toward the north. By repeated morphology analysis and feature tracking, we constrain a spine diameter of ~300 m, extruding at a velocity of 1.7 m/day and discharge rate of 0.3–0.7 m³/s. Particle modeling of an extruding conduit plug highlights that the spine may have inclined to the north due to the topography and hidden architecture of the subsurface. We suggest that such complexities are rather common, where mechanical heterogeneities in the conduit material, mechanical erosion of the hidden spine buried by the co-evolving dome, as well as topographic (un-)buttressing controls directionality of spine growth and spine instability. The results presented here are relevant for understanding the growth and collapse hazards of spines and provide unique insights into the hidden magma-conduit architecture.
Keywords: Shiveluch volcano; Kamchatka